Towards a Mindanawon/Lumad philosophy: The Filipino philosophy of Karl Gaspar - Imbong, Jerry (Animo Repository, 2023)
The anthropologist, sociologist, theologian, and missionary Karl Gaspar, CSsR spend more than half of his life with Lumad communities in Mindanao. His voluminous researches and published works are fruits of his engagements with the Lumad struggle for land, life, and freedom. This paper elucidates Karl Gaspar’s Filipino philosophy extracted from his published books and other writings. The dissertation is composed of four parts: First, it investigates how Gaspar’s biography shaped his philosophical outlook in life. Second, it establishes Karl Gaspar as a philosopher and his ideas as philosophical. Third, it crystallizes Gaspar’s philosophical discourses in the areas of philosophical anthropology, Mindanawon/indigenous ethics, religion and spirituality, and politics and society. And lastly, it highlights Gaspar’s unique contribution to the development of Filipino philosophy in the country, namely, Mindanawon/Lumad philosophy, philosophical saganism, and philosophy of social sciences.